2007
DOI: 10.2460/ajvr.68.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a combined transcutaneous carbon dioxide pressure and pulse oximetry sensor in adult sheep and dogs

Abstract: The tcPCO(2) sensor overestimated PaCO(2) in sheep and dogs and followed changes in PaCO(2) with a considerable lag time. The tcPCO(2) sensor might be useful for noninvasive monitoring of changes but cannot be used as a surrogate measure for PaCO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…In the present study, PtcCO 2 measurements averaged approximately 20% (9 mm Hg) higher than PaCO 2 measurements. There are very few published studies investigating the use of transcutaneous blood gas monitoring in dogs; however, a study investigating 8 adult dogs anesthetized for orthopedic surgery found a mean ± SD difference between PtcCO 2 and PaCO 2 of 8.9 ± 12 mm Hg 10 minutes after sensor application . Thus, that transcutaneous blood gas monitor also over‐estimated PaCO 2 in that group of dogs and had unacceptably large variability in the measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, PtcCO 2 measurements averaged approximately 20% (9 mm Hg) higher than PaCO 2 measurements. There are very few published studies investigating the use of transcutaneous blood gas monitoring in dogs; however, a study investigating 8 adult dogs anesthetized for orthopedic surgery found a mean ± SD difference between PtcCO 2 and PaCO 2 of 8.9 ± 12 mm Hg 10 minutes after sensor application . Thus, that transcutaneous blood gas monitor also over‐estimated PaCO 2 in that group of dogs and had unacceptably large variability in the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, that transcutaneous blood gas monitor also over‐estimated PaCO 2 in that group of dogs and had unacceptably large variability in the measurements. However, the monitor had an acceptable lag time (6.2 min) during the adjustment from normal to hyperventilation . Therefore, the authors cautioned against the use of the monitor to replace PaCO 2 measurements, but recommended that it instead be used to trend PCO 2 values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a range was deemed clinically inaccurate by some, but not all, authors of the aforementioned studies. One study evaluating the use of PtcCO 2 measurements in inhalant anesthetized sheep and dogs found an even greater magnitude of difference from PaCO 2 (Vogt et al. 2007).…”
Section: Discussionmentioning
confidence: 99%